Droplet-based microfluidic synthesis of nanogels for controlled drug delivery: tailoring nanomaterial properties via pneumatically actuated flow-focusing junction. Issue 31 (29th July 2022) - Giannitelli, Sara Maria; Limiti, Emanuele; Mozetic, Pamela; Pinelli, Filippo; Han, Xiaoyu; Abbruzzese, Franca; Basoli, Francesco; Del Rio, Danila; Scialla, Stefano; Rossi, Filippo; Trombetta, Marcella; Rosanò, Laura; et al.
Abstract : A droplet-based microfluidic process relying on an actuated flow-focusing device was used for the in-flow synthesis of hyaluronic acid-polyethyleneimine nanogels with improved drug delivery properties. Abstract : Conventional batch syntheses of polymer-based nanoparticles show considerable shortcomings in terms of scarce control over nanomaterials morphology and limited lot-to-lot reproducibility. Droplet-based microfluidics represents a valuable strategy to overcome these constraints, exploiting the formation of nanoparticles within discrete microdroplets. In this work, we synthesized nanogels (NGs) composed of hyaluronic acid and polyethyleneimine using a microfluidic flow-focusing device endowed with a pressure-driven micro-actuator. The actuator achieves real-time modulation of the junction orifice width, thereby regulating the microdroplet diameter and, as a result, the NG size. Acting on process parameters, NG hydrodynamic diameter could be tuned in the range 92–190 nm while preserving an extremely low polydispersity (0.015); those values are hardly achievable in batch syntheses and underline the strength of our toolbox for the continuous in-flow synthesis of nanocarriers. Furthermore, NGs were validated in vitro as a drug delivery system in a representative case study still lacking an effective therapeutic treatment: ovarian cancer. Using doxorubicin as a chemotherapeutic agent, we show that NG-mediated release of the drug results in an enhanced antiblastic effect vs . the non-encapsulated administration route even at sublethal dosages, highlighting the wide applicability of our microfluidics-enabled nanomaterials in healthcare scenarios.